An efficient method to improve simultaneously the water resistance, flame retardancy and mechanical properties of POE intumescent flame-retardant systems. Issue 21 (6th March 2015) - Li, Rui-Min; Deng, Cong; Deng, Cheng-Liang; Dong, Liang-Ping; Di, Hong-Wei; Wang, Yu-Zhong
<x xml:space="preserve">Abstract</x> The water resistance, flame retardancy and mechanical properties of POE intumescent flame-retardant systems were improved simultaneously.